Preparation method of lithium cobalt oxide material, lithium cobalt oxide material and secondary battery

By pickling and multi-layer coating of lithium cobalt oxide, the problem of poor circulation stability of lithium cobalt oxide during high voltage cycle and storage process is solved, and the surface structure stability and cycling performance of the material are improved.

CN119833625AActive Publication Date: 2025-04-15GUANGDONG BRUNP RECYCLING TECH CO LTD +1

Patent Information

Application Number
CN202510091744.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-15
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

The existing lithium cobalt oxide positive electrode materials have poor cycle stability during high voltage cycle and storage, resulting in a sharp attenuation of capacity. The main reasons are irreversible loss of reactive oxygen species and phase change in the surface structure of the material, as well as polarization caused by cobalt dissolution and SEI film thickening.

Method used

After pickling the lithium cobalt oxide, the phosphate and ammonium fluorate salt are coated successively to form two coated layers to stabilize the surface structure of the lithium cobalt oxide.

Benefits of technology

The surface structure stability and cyclic performance of lithium cobalt oxide materials have been improved, reducing capacity loss and polarization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833625A_ABST
    Figure CN119833625A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a lithium cobalt oxide material, the lithium cobalt oxide material and a secondary battery, and belongs to the field of positive electrode materials. The lithium cobalt oxide material which is stable in surface structure and good in cycle performance is prepared through acid leaching, phosphate primary coating and fluorine acid ammonium salt secondary coating of lithium cobalt oxide in sequence. The lithium cobalt oxide reacts with H < + > in the acid solution in the acid leaching process, and active sites are formed on the surface of the lithium cobalt oxide; pO4 < 3-> in the phosphate reacts with active sites in the subsequent primary coating process to form stably combined primary coated lithium cobalt oxide, and the phosphate is distributed on the surface of the lithium cobalt oxide in a dotted manner, so that the corrosion of an electrolyte can be inhibited; in the secondary coating process, NH4 < + > in the ammonium fluoride salt is combined with surface O < 2-> of an uncoated area on the surface of the primary coated lithium cobalt oxide to generate water and ammonia gas, so that a tightly coated fluoride coating layer is formed, and the fluoride coating layer can effectively reduce corrosion of hydrofluoric acid generated by electrolyte decomposition to the positive electrode material, reduce release of oxygen on the surface layer and improve the service life of the positive electrode material. The surface structure of the lithium cobalt oxide material is further stabilized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of positive electrode materials, and in particular to a preparation method of a lithium cobalt oxide material, a lithium cobalt oxide material and a secondary battery. Background Art

[0002] Lithium cobalt oxide (LiCoO2) is widely used in 3C electronic products due to its high compaction density. 3C electronic products are developing towards multifunctionality, miniaturization and intelligence, which puts forward higher requirements on the volume energy density of lithium-ion batteries.

[0003] At present, LiCoO2 cathode materials can effectively improve the specific capacity of batteries by further increasing the charging voltage on the 4.50V voltage platform, but it will cause a sharp attenuation of capacity during cycling and high-temperature storage; poor cycling stability is also the main reason restricting the application of high-voltage, high-specific-capacity LiCoO2 cathode materials. The irreversible loss of active oxygen during high-voltage cycling and storage of materials leads to phase changes in the surface structure of the materials, and the dissolution of cobalt on the surface of the materials and the continuous thickening of the catalytic SEI film deposited on the negative electrode side lead to polarization of the battery, which are two important factors causing capacity loss and cycle failure.

[0004] How to reasonably control the surface structure of high-voltage LiCoO2 positive electrode materials is the key to improving the cycle and high-temperature storage performance of high-voltage LiCoO2 positive electrode materials. At present, the industry generally uses the solid phase method to prepare lithium cobalt oxide. The solid phase coating material is easy to fall off during the high-voltage cycle, affecting the cycle stability; at the same time, studies have shown that using only fluoride, phosphate or oxide as a coating cannot completely solve the interface problem of lithium cobalt oxide under high voltage.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The purpose of the present invention includes providing a preparation method of a lithium cobalt oxide material, a lithium cobalt oxide material and a secondary battery. After the lithium cobalt oxide is pickled, it is coated with phosphate and ammonium fluoride salt in sequence. After two coatings, a lithium cobalt oxide material with a stable surface structure and good cycle performance is obtained.

[0007] In order to achieve the above-mentioned object, the present invention provides a method for preparing a lithium cobalt oxide material in a first aspect, comprising: pre-treatment of the lithium cobalt oxide: dispersing the lithium cobalt oxide in an acid solution for stirring reaction, and then filtering, washing and drying to obtain acid-treated lithium cobalt oxide; Primary coating: the acid-treated lithium cobalt oxide is mixed with phosphate and then sintered once to obtain primary coated lithium cobalt oxide; Secondary coating: The primary coated lithium cobalt oxide is mixed with ammonium fluoride salt and then sintered for a secondary time to obtain a lithium cobalt oxide material.

[0008] In some embodiments, the acid in the acid solution includes at least one of oxalic acid, acetic acid, citric acid, phosphoric acid, and carbonic acid; and / or, the phosphate comprises at least one of Li3PO4, LiCoPO4, LiFePO4, LiNiPO4, LiH2PO4, Co3(PO4)2 and LiH2PO4; And / or, the ammonium fluoride salt includes at least one of NH4BF4, (NH4)3AlF6, (NH4)2SiF6 and (NH4)2GeF6.

[0009] In some embodiments, the molar concentration of the acid solution is 0.01-0.20 mol / L; and / or, the phosphate is 1wt%-3wt% of the acid-treated lithium cobalt oxide; And / or, the ammonium fluoride salt is 0.1wt%-0.5wt% of the primary coated lithium cobalt oxide.

[0010] In some embodiments, the lithium cobalt oxide includes large-particle lithium cobalt oxide and small-particle lithium cobalt oxide, and the large-particle lithium cobalt oxide satisfies 18 μm ≤ D v 50≤21μm, the small particle lithium cobalt oxide satisfies 4.5μm≤Dv50≤9.5μm; The solid-liquid mass ratio of the lithium cobalt oxide to the acid solution is 1:1-3.

[0011] In some embodiments, the primary sintering temperature is 500-900° C. and the time is 3-6 hours; And / or, the secondary sintering temperature is 400-800°C and the time is 3-6h; And / or, the drying temperature is 60-120°C and the drying time is 24-30h; And / or, the stirring reaction time is 5-10 min.

[0012] In some embodiments, the preparation process of the lithium cobalt oxide includes: mixing a lithium source and an additive with large-particle cobalt oxide and small-particle cobalt oxide, respectively, and then sintering and crushing to obtain the large-particle lithium cobalt oxide and the small-particle lithium cobalt oxide, respectively.

[0013] In some embodiments, the large particles of cobalt oxide satisfy 13.5 μm ≤ D v 50≤18.5μm; And / or, the small particles of cobalt oxide satisfy 1.5 μm ≤ D v 50≤6.5μm; and / or, the additive is an oxide, the oxide comprising at least one of the elements Ti, Mg, Al, Y, La, Zr and B; And / or, the lithium source includes at least one of lithium carbonate and lithium hydroxide.

[0014] In some embodiments, the additive is 0.3 wt%-3.5 wt% of the large cobalt oxide particles or the small cobalt oxide particles; and / or, the molar ratio of the lithium element in the lithium source to the cobalt element in the large cobalt oxide particles or the small cobalt oxide particles is 1.07-1.09; And / or, the sintering temperature is 1050-1100°C.

[0015] A second aspect of the present invention provides a lithium cobalt oxide material, which is prepared by the preparation method provided by the first aspect of the present invention.

[0016] A third aspect of the present invention provides a secondary battery, wherein the secondary battery comprises the lithium cobalt oxide material provided by the second aspect of the present invention.

[0017] The beneficial effects of the present invention include: The present invention provides a method for preparing a lithium cobalt oxide material. Lithium cobalt oxide is successively acid-leached, coated with phosphate once, and coated with ammonium fluoride twice to prepare a lithium cobalt oxide material with a stable surface structure and good cycle performance. + React and form active sites on its surface; in the subsequent coating process, PO4 in the phosphate 3- Phosphates react with active sites to form a stable primary coated lithium cobalt oxide. Phosphates are distributed on the surface of lithium cobalt oxide in a dotted manner, which can effectively inhibit the corrosion of the electrolyte. During the secondary coating process, NH 4+ The surface O of the unsalted area of ​​the primary coated lithium cobalt oxide surface 2- The combination generates water and ammonia, thereby forming a tightly wrapped fluoride coating. The fluoride coating can effectively reduce the corrosion of the positive electrode material by the hydrofluoric acid produced by the decomposition of the electrolyte, reduce the release of surface oxygen, and further stabilize the surface structure of the lithium cobalt oxide material. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0019] Figure 1 This is a SEM image of the lithium cobalt oxide material provided in Example 1 of the present invention; Figure 2 This is a SEM image of the lithium cobalt oxide material provided in Example 2 of the present invention; Figure 3 An EDS graph of the element P of the lithium cobalt oxide material provided in Example 1 of the present invention; Figure 4 An EDS graph of element F of the lithium cobalt oxide material provided in Example 1 of the present invention; Figure 5 This is the XRD diagram of the lithium cobalt oxide material provided in Example 1 of the present invention. DETAILED DESCRIPTION

[0020] Hereinafter, a method for preparing a lithium cobalt oxide material, a lithium cobalt oxide material and a secondary battery of the present invention will be specifically disclosed with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0021] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. In particular, "()", ")", "[" and "]" represent intervals, where "(" or ")" represents an open interval, that is, the endpoint values ​​of the interval are not included; "[" and "]" represent a closed interval, that is, the endpoints within the interval are included. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range.

[0022] Specifically, for example, if a range of 60-120 and 80-110 is listed for a particular parameter, it is understood that the range of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range "ab" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" have been fully listed in this article, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a certain parameter is expressed as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc. If (10, 20) is listed, it is understood as any value between 10 and 20, excluding 10 and 20; (10, 20] is understood as any value between 10 and 20, excluding 10 but including 20.

[0023] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0024] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0025] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0026] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0027] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0028] The present invention provides a method for preparing a lithium cobalt oxide material, comprising: Pretreatment of lithium cobalt oxide: dispersing lithium cobalt oxide in an acid solution for stirring reaction, and then filtering, washing and drying to obtain acid-treated lithium cobalt oxide; Primary coating: the acid-treated lithium cobalt oxide is mixed with phosphate and then sintered once to obtain primary coated lithium cobalt oxide; Secondary coating: The primary coated lithium cobalt oxide is mixed with ammonium fluoride salt and then sintered for a secondary time to obtain a lithium cobalt oxide material.

[0029] The present invention provides a method for preparing a lithium cobalt oxide material. The lithium cobalt oxide is sequentially subjected to acid leaching, primary phosphate coating and secondary ammonium fluoride coating to prepare a lithium cobalt oxide material with a stable surface structure and good cycle performance. During the acid leaching process, the acid solution etches the surface of the lithium cobalt oxide, and the H + Reacts with lithium cobalt oxide and forms lithium vacancies and oxygen vacancies on its surface; in the subsequent encapsulation process, PO4 3- Enter the oxygen vacancies, and lithium ions enter the lithium vacancies to form a primary coated lithium cobalt oxide with stable bonding. Since phosphate coating easily forms agglomerates on the surface of the material during the coating process, only one coating cannot achieve complete coating of the lithium cobalt oxide material, and there is an exposed surface that is not coated. During the secondary coating process, NH 4+ Compared with the bare surface of the primary coated lithium cobalt oxide that is not coated with phosphate, the O 2- The combination produces water and ammonia, which in turn form a tightly packed fluoride coating.

[0030] Phosphate coating can effectively inhibit the corrosion of lithium cobalt oxide by electrolyte, and fluoride coating can effectively reduce the corrosion of positive electrode materials by hydrofluoric acid produced by the decomposition of electrolyte, reduce the release of surface oxygen, and further stabilize the surface structure of lithium cobalt oxide materials, which is beneficial to improving the cycle performance of lithium cobalt oxide materials.

[0031] In some embodiments, the acid in the acid solution includes at least one of oxalic acid, acetic acid, citric acid, phosphoric acid and carbonic acid. The acids in the acid solution are all weak acids. Compared with weak acids, strong acids may react more violently with the particle surface to produce unnecessary by-products, thereby affecting the quality and performance of the final product.

[0032] In some embodiments, the phosphate includes at least one of Li3PO4, LiCoPO4, LiFePO4, LiNiPO4, LiH2PO4, Co3(PO4)2, and LiH2PO4.

[0033] In some embodiments, the ammonium fluoride salt includes at least one of NH4BF4, (NH4)3AlF6, (NH4)2SiF6, and (NH4)2GeF6.

[0034] In some embodiments, the molar concentration of the acid solution is 0.01-0.20 mol / L. Too high or too low a concentration of the acid solution will affect the etching effect of the material; if the concentration of the acid solution is too high, the etching degree will be too high, resulting in serious capacity loss of the positive electrode material; if the concentration of the acid solution is too low, it is insufficient to form effective etching, further affecting the coating effect of the phosphate.

[0035] In some embodiments, the phosphate is 1 wt % to 3 wt % of the acid-treated lithium cobalt oxide.

[0036] In some embodiments, the ammonium fluoride salt is used to coat the lithium cobaltate at 0.1 wt % to 0.5 wt %.

[0037] In some embodiments, the lithium cobalt oxide includes large-particle lithium cobalt oxide and small-particle lithium cobalt oxide, and the large-particle lithium cobalt oxide satisfies 18 μm ≤ D v 50≤21μm, and the small particle lithium cobalt oxide satisfies 4.5μm≤Dv50≤9.5μm.

[0038] In some embodiments, the solid-liquid mass ratio of lithium cobalt oxide to the acid solution is 1:1-3.

[0039] In some embodiments, the primary sintering temperature is 500-900° C. and the time is 3-6 hours.

[0040] In some embodiments, the secondary sintering is performed at a temperature of 400-800° C. and for a time of 3-6 hours.

[0041] In some embodiments, the drying temperature is 60-120° C. and the drying time is 24-30 h.

[0042] In some embodiments, the stirring reaction time is 5-10 min.

[0043] In some embodiments, the preparation process of lithium cobalt oxide includes: mixing a lithium source and an additive with large cobalt oxide particles and small cobalt oxide particles, respectively, and then sintering and crushing to obtain large cobalt oxide particles and small cobalt oxide particles, respectively.

[0044] The lithium source and the additive are mixed with large-particle cobalt oxide and small-particle cobalt oxide respectively, and then sintered and crushed to obtain doped lithium cobalt oxide material, namely large-particle lithium cobalt oxide and small-particle lithium cobalt oxide. After doping, the bulk lattice distortion of the material can be alleviated and the stability of the material can be improved.

[0045] In some embodiments, the large particles of cobalt oxide satisfy 13.5 μm ≤ D v 50≤18.5μm.

[0046] In some embodiments, the small particles of cobalt oxide satisfy 1.5 μm ≤ D v 50≤6.5μm.

[0047] In some embodiments, the additive is an oxide, and the oxide includes at least one of the elements Ti, Mg, Al, Y, La, Zr and B.

[0048] In some embodiments, the lithium source includes at least one of lithium carbonate and lithium hydroxide.

[0049] In some embodiments, the additive is 0.3 wt % to 3.5 wt % of the large particle cobalt oxide or the small particle cobalt oxide.

[0050] In some embodiments, the molar ratio of the lithium element in the lithium source to the cobalt element in the large-particle cobalt oxide or the small-particle cobalt oxide is 1.07-1.09.

[0051] In some embodiments, the sintering temperature is 1050-1100°C.

[0052] The second aspect of the present invention provides a lithium cobalt oxide material, the lithium cobalt oxide material is prepared by the preparation method provided by the first aspect of the present invention, and the lithium cobalt oxide material satisfies 16μm≤D v 50≤18μm.

[0053] A third aspect of the present invention provides a secondary battery, wherein the secondary battery comprises the lithium cobalt oxide material provided by the second aspect of the present invention.

[0054] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0055] The features and properties of the present invention are further described in detail below in conjunction with the examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention.

[0056] Example 1 (1) Preparation of lithium cobalt oxide: Preparation of large-particle lithium cobalt oxide: D v After the large particles of 15.5 μm cobalt oxide, lithium carbonate and additives are mixed evenly, they are sintered in a high-temperature box furnace at 1070°C for 10 hours in an air atmosphere. After cooling, they are roughly crushed by a double roller mill and finely crushed by an air flow mill to obtain D v 50 is a large-particle lithium cobalt oxide with a size of 18.8 μm. The additive is a mixture of aluminum, zirconium and titanium in a mass ratio of 2:1:1, the molar ratio of lithium in lithium carbonate to cobalt in large-particle cobalt oxide is 1.08:1, and the additive is 2.3wt% of the large-particle cobalt oxide.

[0057] Preparation of small particles of lithium cobalt oxide: D v After the small particles of 3.2μm cobalt oxide, lithium carbonate and additives are mixed evenly, they are sintered in a high-temperature box furnace at 1020℃ in an air atmosphere for 10 hours. After cooling, they are roughly crushed by a roller mill and finely crushed by an air flow mill to obtain D v 50 is a small particle of lithium cobalt oxide with a size of 5.5 μm. The additive is a mixture of aluminum, zirconium and titanium in a mass ratio of 2:1:1, the molar ratio of lithium in lithium carbonate to cobalt in small particles of cobalt tetroxide is 1.08:1, and the additive is 1.2wt% of the small particles of cobalt tetroxide.

[0058] (2) Pretreatment of lithium cobalt oxide: large-particle lithium cobalt oxide and small-particle lithium cobalt oxide are mixed in a mass ratio of 4:1, and the mixed lithium cobalt oxide is dispersed in a 0.1 mol / L citric acid solution in a solid-liquid mass ratio of 1:2, and stirred at room temperature for 10 minutes. The material is then filtered and washed twice with deionized water, and then dried in an oven at 80°C for 24 hours to obtain acid-treated lithium cobalt oxide; (3) Primary coating: After mixing the acid-treated lithium cobalt oxide and lithium phosphate, the mixture is sintered in a high-temperature box furnace at 800°C for 6 hours in an air atmosphere, cooled and mechanically crushed to obtain a primary coated lithium cobalt oxide; the lithium phosphate is 1wt% of the acid-treated lithium cobalt oxide; (4) Secondary coating: The primary coated lithium cobalt oxide and ammonium fluoroaluminate are mixed, and then secondary sintered in a high-temperature box furnace at 700°C for 6 hours under air atmosphere. After cooling, the mixture is mechanically crushed to obtain a lithium cobalt oxide material; the ammonium fluoroaluminate is 0.2wt% of the primary coated lithium cobalt oxide.

[0059] Example 2 The only difference between this embodiment and embodiment 1 is that the molar concentration of citric acid in step (2) is 0.2 mol / L, and the other steps are the same as those in embodiment 1.

[0060] Example 3 The only difference between this embodiment and embodiment 1 is that the molar concentration of citric acid in step (2) is 0.05 mol / L, and the other steps are the same as those in embodiment 1.

[0061] Example 4 The only difference between this embodiment and embodiment 1 is that the phosphate in step (3) is Co3(PO4)2, and the other steps are the same as those in embodiment 1.

[0062] Example 5 The only difference between this embodiment and embodiment 1 is that the phosphate in step (3) is LiH2PO4, and the other steps are the same as those in embodiment 1.

[0063] Example 6 The only difference between this embodiment and embodiment 1 is that the ammonium fluoride salt in step (4) is NH4BF4, and the other steps are the same as those in embodiment 1.

[0064] Example 7 The only difference between this embodiment and embodiment 1 is that the ammonium fluoride salt in step (4) is (NH4)2SiF6, and the other steps are the same as those in embodiment 1.

[0065] Example 8 (1) Preparation of lithium cobalt oxide: Preparation of large-particle lithium cobalt oxide: D v After the large particles of 13.5 μm cobalt oxide, lithium carbonate and additives are mixed evenly, they are sintered in a high-temperature box furnace at 1070°C for 10 hours in an air atmosphere. After cooling, they are roughly crushed by a double roller mill and finely crushed by an air flow mill to obtain D v 50 is a large particle of lithium cobalt oxide with a size of 16.5 μm. The additive is a mixture of aluminum, zirconium and titanium in a mass ratio of 2:1:1, the molar ratio of lithium in lithium carbonate to cobalt in large particles of cobalt tetroxide is 1.08:1, and the additive is 0.3wt% of the large particles of cobalt tetroxide.

[0066] Preparation of small particles of lithium cobalt oxide: D v After the small particles of 1.5 μm cobalt oxide, lithium carbonate and additives are mixed evenly, they are sintered in a high-temperature box furnace at 1020°C for 10 hours in an air atmosphere. After cooling, they are roughly crushed by a double roller mill and finely crushed by an air flow mill to obtain D v 50 is a small particle of lithium cobalt oxide with a size of 3.3 μm. The additive is a mixture of aluminum, zirconium and titanium in a mass ratio of 2:1:1, the molar ratio of lithium in lithium carbonate to cobalt in small particles of cobalt tetroxide is 1.08:1, and the additive is 0.3wt% of the small particles of cobalt tetroxide.

[0067] (2) Pretreatment of lithium cobalt oxide: large-particle lithium cobalt oxide and small-particle lithium cobalt oxide are mixed in a mass ratio of 4:1, and the mixed lithium cobalt oxide is dispersed in a 0.01 mol / L oxalic acid solution in a solid-liquid mass ratio of 1:3, and stirred at room temperature for 10 minutes. The material is then filtered and washed twice with deionized water, and then dried in an oven at 80°C for 24 hours to obtain acid-treated lithium cobalt oxide; (3) Primary coating: After mixing the acid-treated lithium cobalt oxide and lithium phosphate, the mixture is sintered in a high-temperature box furnace at 500°C for 6 hours in an air atmosphere, cooled and mechanically crushed to obtain a primary coated lithium cobalt oxide; the lithium phosphate is 2.5wt% of the acid-treated lithium cobalt oxide; (4) Secondary coating: The primary coated lithium cobalt oxide and ammonium fluoroaluminate are mixed, and then secondary sintered in an 800°C high-temperature box furnace for 6 hours under air atmosphere. After cooling, the mixture is mechanically crushed to obtain a lithium cobalt oxide material; the ammonium fluoroaluminate is 0.5wt% of the primary coated lithium cobalt oxide.

[0068] Example 9 (1) Preparation of lithium cobalt oxide: Preparation of large-particle lithium cobalt oxide: D v After the large particles of 18.5 μm cobalt oxide, lithium carbonate and additives are mixed evenly, they are sintered in a high-temperature box furnace at 1070°C for 10 hours in an air atmosphere. After cooling, they are roughly crushed by a double roller mill and finely crushed by an air flow mill to obtain D v 50 is a large-particle lithium cobalt oxide with a size of 22 μm. The additive is a mixture of aluminum, zirconium and titanium in a mass ratio of 2:1:1, the molar ratio of lithium in lithium carbonate to cobalt in large-particle cobalt oxide is 1.08:1, and the additive is 3.5wt% of the large-particle cobalt oxide.

[0069] Preparation of small particles of lithium cobalt oxide: D v After the small particles of 6.5μm cobalt oxide, lithium carbonate and additives are mixed evenly, they are sintered in a high-temperature box furnace at 1020℃ in an air atmosphere for 10 hours. After cooling, they are roughly crushed by a roller mill and finely crushed by an air flow mill to obtain D v 50 is a small particle of lithium cobalt oxide with a size of 9 μm. The additive is a mixture of aluminum, zirconium and titanium in a mass ratio of 2:1:1, the molar ratio of lithium in lithium carbonate to cobalt in small particles of cobalt tetroxide is 1.08:1, and the additive is 3.5wt% of the small particles of cobalt tetroxide.

[0070] (2) Pretreatment of lithium cobalt oxide: large-particle lithium cobalt oxide and small-particle lithium cobalt oxide are mixed in a mass ratio of 4:1, and the mixed lithium cobalt oxide is dispersed in a 0.2 mol / L acetic acid solution in a solid-liquid mass ratio of 1:1, and stirred at room temperature for 10 minutes. The material is then filtered and washed twice with deionized water, and then dried in an oven at 80°C for 24 hours to obtain acid-treated lithium cobalt oxide; (3) Primary coating: After mixing the acid-treated lithium cobalt oxide and lithium phosphate, the mixture is sintered in a high-temperature box furnace at 900°C for 6 hours in an air atmosphere, cooled and mechanically crushed to obtain a primary coated lithium cobalt oxide; the lithium phosphate is 3wt% of the acid-treated lithium cobalt oxide; (4) Secondary coating: The primary coated lithium cobalt oxide and ammonium fluoroaluminate are mixed, and then secondary sintered in a high-temperature box furnace at 400°C for 6 hours under air atmosphere. After cooling, the mixture is mechanically crushed to obtain a lithium cobalt oxide material; the ammonium fluoroaluminate is 0.1wt% of the primary coated lithium cobalt oxide.

[0071] Comparative Example 1 (1) Preparation of lithium cobalt oxide: Preparation of large-particle lithium cobalt oxide: D v After the large particles of 15.5 μm cobalt oxide, lithium carbonate and additives are mixed evenly, they are sintered in a high-temperature box furnace at 1070°C for 10 hours in an air atmosphere. After cooling, they are roughly crushed by a double roller mill and finely crushed by an air flow mill to obtain D v 50 is a large-particle lithium cobalt oxide with a size of 18.8 μm. The additive is a mixture of aluminum, zirconium and titanium in a mass ratio of 2:1:1, the molar ratio of lithium in lithium carbonate to cobalt in large-particle cobalt oxide is 1.08:1, and the additive is 2.3wt% of the large-particle cobalt oxide.

[0072] Preparation of small particles of lithium cobalt oxide: D v After the small particles of 3.2μm cobalt oxide, lithium carbonate and additives are mixed evenly, they are sintered in a high-temperature box furnace at 1020℃ in an air atmosphere for 10 hours. After cooling, they are roughly crushed by a roller mill and finely crushed by an air flow mill to obtain D v 50 is a small particle of lithium cobalt oxide with a size of 5.5 μm. The additive is a mixture of aluminum, zirconium and titanium in a mass ratio of 2:1:1, the molar ratio of lithium in lithium carbonate to cobalt in small particles of cobalt tetroxide is 1.08:1, and the additive is 1.2wt% of the small particles of cobalt tetroxide.

[0073] (2) Primary coating: large-particle lithium cobalt oxide and small-particle lithium cobalt oxide are mixed in a mass ratio of 4:1 and then mixed with lithium phosphate. The mixture is sintered in an 800°C high-temperature box furnace for 6 hours under air atmosphere. After cooling, the mixture is mechanically crushed to obtain primary coated lithium cobalt oxide. The lithium phosphate is 1wt% of the total mass of large-particle lithium cobalt oxide and small-particle lithium cobalt oxide. (3) Secondary coating: The primary coated lithium cobalt oxide and ammonium fluoroaluminate are mixed, and then secondary sintered in a high-temperature box furnace at 700°C for 6 hours under air atmosphere. After cooling, the mixture is mechanically crushed to obtain a lithium cobalt oxide material; the ammonium fluoroaluminate is 0.2wt% of the primary coated lithium cobalt oxide.

[0074] Comparative Example 2 (1) Preparation of lithium cobalt oxide: Preparation of large-particle lithium cobalt oxide: After mixing large-particle cobalt oxide with a Dv50 of 15.5μm, lithium carbonate and additives, sinter in a high-temperature box furnace at 1070℃ in an air atmosphere for 10h, and after cooling, crush by a roller mill and air flow mill to obtain large-particle lithium cobalt oxide with a Dv50 of 18.8μm. The additive is mixed according to the mass ratio of aluminum element, zirconium element and titanium element of aluminum oxide, zirconium oxide and titanium oxide of 2:1:1, the molar ratio of lithium element in lithium carbonate and cobalt element in large-particle cobalt oxide is 1.08:1, and the additive is 2.3wt% of large-particle cobalt oxide.

[0075] Preparation of small-particle lithium cobalt oxide: small-particle cobalt oxide with a Dv50 of 3.2 μm, lithium carbonate and additives are uniformly mixed, sintered in a high-temperature box furnace at 1020°C in an air atmosphere for 10 hours, and after cooling, coarse crushing by a roller mill and fine grinding by air flow grinding to obtain small-particle lithium cobalt oxide with a Dv50 of 5.5 μm. The additive is mixed according to the mass ratio of aluminum element, zirconium element and titanium element of aluminum oxide, zirconium oxide and titanium oxide of 2:1:1, the molar ratio of lithium element in lithium carbonate and cobalt element in small-particle cobalt oxide is 1.08:1, and the additive is 1.2wt% of small-particle cobalt oxide.

[0076] (2) Pretreatment of lithium cobalt oxide: large-particle lithium cobalt oxide and small-particle lithium cobalt oxide are mixed in a mass ratio of 4:1, and the mixed lithium cobalt oxide is dispersed in a 0.1 mol / L citric acid solution in a solid-liquid mass ratio of 1:2, and stirred at room temperature for 10 minutes. The material is then filtered and washed twice with deionized water, and then dried in an oven at 80°C for 24 hours to obtain acid-treated lithium cobalt oxide; (3) Coating: After mixing acid-treated lithium cobalt oxide and ammonium fluoroaluminate, the mixture is subjected to secondary sintering in a high-temperature box furnace at 700°C for 6 hours under air atmosphere. After cooling, the mixture is mechanically crushed to obtain a lithium cobalt oxide material; the ammonium fluoroaluminate is 0.2wt% of the acid-treated lithium cobalt oxide.

[0077] Comparative Example 3 (1) Preparation of lithium cobalt oxide: Preparation of large-particle lithium cobalt oxide: D v After the large particles of 15.5 μm cobalt oxide, lithium carbonate and additives are mixed evenly, they are sintered in a high-temperature box furnace at 1070°C for 10 hours in an air atmosphere. After cooling, they are roughly crushed by a double roller mill and finely crushed by an air flow mill to obtain D v 50 is a large-particle lithium cobalt oxide with a size of 18.8 μm. The additive is a mixture of aluminum, zirconium and titanium in a mass ratio of 2:1:1, the molar ratio of lithium in lithium carbonate to cobalt in large-particle cobalt oxide is 1.08:1, and the additive is 2.3wt% of the large-particle cobalt oxide.

[0078] Preparation of small particles of lithium cobalt oxide: D v After the small particles of 3.2μm cobalt oxide, lithium carbonate and additives are mixed evenly, they are sintered in a high-temperature box furnace at 1020℃ in an air atmosphere for 10 hours. After cooling, they are roughly crushed by a roller mill and finely crushed by an air flow mill to obtain D v 50 is a small particle of lithium cobalt oxide with a size of 5.5 μm. The additive is a mixture of aluminum, zirconium and titanium in a mass ratio of 2:1:1, the molar ratio of lithium in lithium carbonate to cobalt in small particles of cobalt tetroxide is 1.08:1, and the additive is 1.2wt% of the small particles of cobalt tetroxide.

[0079] (2) Pretreatment of lithium cobalt oxide: large-particle lithium cobalt oxide and small-particle lithium cobalt oxide are mixed in a mass ratio of 4:1, and the mixed lithium cobalt oxide is dispersed in a 0.1 mol / L citric acid solution in a solid-liquid mass ratio of 1:2, and stirred at room temperature for 10 minutes. The material is then filtered and washed twice with deionized water, and then dried in an oven at 80°C for 24 hours to obtain acid-treated lithium cobalt oxide; (3) Coating: After mixing acid-treated lithium cobalt oxide and lithium phosphate, the mixture is sintered in a high-temperature box furnace at 800°C for 6 hours under air atmosphere, cooled and mechanically crushed to obtain lithium cobalt oxide material; the lithium phosphate is 1wt% of the acid-treated lithium cobalt oxide; Comparative Example 4 (1) Preparation of lithium cobalt oxide: Preparation of large-particle lithium cobalt oxide: D v After the large particles of 15.5 μm cobalt oxide, lithium carbonate and additives are mixed evenly, they are sintered in a high-temperature box furnace at 1070°C for 10 hours in an air atmosphere. After cooling, they are roughly crushed by a double roller mill and finely crushed by an air flow mill to obtain D v50 is a large-particle lithium cobalt oxide with a size of 18.8 μm. The additive is a mixture of aluminum, zirconium and titanium in a mass ratio of 2:1:1, the molar ratio of lithium in lithium carbonate to cobalt in large-particle cobalt oxide is 1.08:1, and the additive is 2.3wt% of the large-particle cobalt oxide.

[0080] Preparation of small particles of lithium cobalt oxide: D v After the small particles of 3.2μm cobalt oxide, lithium carbonate and additives are mixed evenly, they are sintered in a high-temperature box furnace at 1020℃ in an air atmosphere for 10 hours. After cooling, they are roughly crushed by a roller mill and finely crushed by an air flow mill to obtain D v 50 is a small particle of lithium cobalt oxide with a size of 5.5 μm. The additive is a mixture of aluminum, zirconium and titanium in a mass ratio of 2:1:1, the molar ratio of lithium in lithium carbonate to cobalt in small particles of cobalt tetroxide is 1.08:1, and the additive is 1.2wt% of the small particles of cobalt tetroxide.

[0081] (2) Lithium cobalt oxide treatment: Large-particle lithium cobalt oxide and small-particle lithium cobalt oxide are mixed in a mass ratio of 4:1, and then the mixed lithium cobalt oxide is dispersed in a 0.1 mol / L citric acid solution in a solid-liquid mass ratio of 1:2. The mixture is stirred and reacted at room temperature for 10 min. The material is then filtered and washed twice with deionized water, and then baked in an oven at 80°C for 24 hours to obtain a lithium cobalt oxide material.

[0082] Comparative Example 5 (1) Preparation of lithium cobalt oxide: Preparation of large-particle lithium cobalt oxide: D v After the large particles of 15.5 μm cobalt oxide, lithium carbonate and additives are mixed evenly, they are sintered in a high-temperature box furnace at 1070°C for 10 hours in an air atmosphere. After cooling, they are roughly crushed by a double roller mill and finely crushed by an air flow mill to obtain D v 50 is a large-particle lithium cobalt oxide with a size of 18.8 μm. The additive is a mixture of aluminum, zirconium and titanium in a mass ratio of 2:1:1, the molar ratio of lithium in lithium carbonate to cobalt in large-particle cobalt oxide is 1.08:1, and the additive is 2.3wt% of the large-particle cobalt oxide.

[0083] Preparation of small particles of lithium cobalt oxide: D v After the small particles of 3.2μm cobalt oxide, lithium carbonate and additives are mixed evenly, they are sintered in a high-temperature box furnace at 1020℃ in an air atmosphere for 10 hours. After cooling, they are roughly crushed by a roller mill and finely crushed by an air flow mill to obtain D v50 is a small particle of lithium cobalt oxide with a size of 5.5 μm. The additive is a mixture of aluminum, zirconium and titanium in a mass ratio of 2:1:1, the molar ratio of lithium in lithium carbonate to cobalt in small particles of cobalt tetroxide is 1.08:1, and the additive is 1.2wt% of the small particles of cobalt tetroxide.

[0084] (2) Coating: Large-particle lithium cobalt oxide and small-particle lithium cobalt oxide are mixed in a mass ratio of 4:1 and then mixed with lithium phosphate. The mixture is sintered in a high-temperature box furnace at 800°C for 6 hours under air atmosphere. After cooling, the mixture is mechanically crushed to obtain a lithium cobalt oxide material. The lithium phosphate is 1wt% of the total mass of the large-particle lithium cobalt oxide and the small-particle lithium cobalt oxide. Comparative Example 6 (1) Preparation of lithium cobalt oxide: Preparation of large-particle lithium cobalt oxide: D v After the large particles of 15.5 μm cobalt oxide, lithium carbonate and additives are mixed evenly, they are sintered in a high-temperature box furnace at 1070°C for 10 hours in an air atmosphere. After cooling, they are roughly crushed by a double roller mill and finely crushed by an air flow mill to obtain D v 50 is a large-particle lithium cobalt oxide with a size of 18.8 μm. The additive is a mixture of aluminum, zirconium and titanium in a mass ratio of 2:1:1, the molar ratio of lithium in lithium carbonate to cobalt in large-particle cobalt oxide is 1.08:1, and the additive is 2.3wt% of the large-particle cobalt oxide.

[0085] Preparation of small particles of lithium cobalt oxide: D v After the small particles of 3.2μm cobalt oxide, lithium carbonate and additives are mixed evenly, they are sintered in a high-temperature box furnace at 1020℃ in an air atmosphere for 10 hours. After cooling, they are roughly crushed by a roller mill and finely crushed by an air flow mill to obtain D v 50 is a small particle of lithium cobalt oxide with a size of 5.5 μm. The additive is a mixture of aluminum, zirconium and titanium in a mass ratio of 2:1:1, the molar ratio of lithium in lithium carbonate to cobalt in small particles of cobalt tetroxide is 1.08, and the additive is 1.2wt% of the small particles of cobalt tetroxide.

[0086] (2) Coating: Large-particle lithium cobalt oxide and small-particle lithium cobalt oxide are mixed in a mass ratio of 4:1, and then mixed with ammonium fluoroaluminate. The mixture is sintered for 6 hours in a high-temperature box furnace at 700°C under air atmosphere. After cooling, the mixture is mechanically crushed to obtain a lithium cobalt oxide material; the ammonium fluoroaluminate is 0.2wt% of the total mass of the large-particle lithium cobalt oxide and the small-particle lithium cobalt oxide.

[0087]

Performance test

[0088] (2) Characterization of coating properties: The EDS graph of P and F elements on the surface of the lithium cobalt oxide material provided in Example 1 of the present invention was characterized using a scanning electron microscope-energy dispersive spectrometer. Figure 3 and Figure 4 The EDS diagram of the P element and the F element of the lithium cobalt oxide material provided in Example 1 shows that in the same area, the P element exists on the surface of the lithium cobalt oxide material and is aggregated in blocks ( Figure 3 ), which is caused by the agglomeration of phosphate during the sintering process; in addition, there are F elements distributed in the uncovered areas of P elements on the surface of the lithium cobalt oxide material ( Figure 4 ), that is, the uncovered area of ​​the primary-coated lithium cobalt oxide coated with ammonium fluoride salt.

[0089] (3) Structural characterization: The structure of the lithium cobalt oxide material provided in Example 1 was characterized by using an X-ray diffractometer. Figure 5 This is the XRD diagram of lithium cobalt oxide material. It can be seen from the figure that the crystal structure of lithium cobalt oxide material is good.

[0090] 2. Electrochemical performance test Preparation of button half-cell: lithium cobalt oxide material, conductive carbon, polyvinylidene fluoride are mixed evenly with deionized water in a mass ratio of 95:2:3 and coated on aluminum foil to obtain a positive electrode. 1 mol / L LiPF6 is dissolved in EC and DEC mixed in a volume ratio of 1:1, and then 3 wt% FEC is added to obtain an electrolyte; the separator is a PP / PE / PP composite film. The above positive electrode, lithium sheet negative electrode, the above electrolyte and the separator are made into a button half-cell; the button half-cell test voltage is 2.3-4.58V.

[0091] Preparation of button-type full battery: lithium cobalt oxide material, conductive carbon and polyvinylidene fluoride are mixed evenly with deionized water in a mass ratio of 95:2:3 and coated on aluminum foil to obtain a positive electrode. 1 mol / L LiPF6 is dissolved in EC and DEC mixed in a volume ratio of 1:1, and then 3 wt% FEC is added to obtain an electrolyte; the separator is a PP / PE / PP composite film. The above positive electrode, graphite negative electrode, the above electrolyte and separator are made into a button-type full battery; the button-type full battery test voltage is 3.0-4.53V, and the current density is 1 / 3C.

[0092] (1) By preparing a button-type half-cell, the first discharge specific capacity and the first coulombic efficiency of each embodiment and comparative example were measured, and the results are shown in Table 1; (2) By preparing button-type full batteries, it was found that the o and 45 o C cycle performance, and at 45 o The storage performance of C is shown in Table 1.

[0093] Table 1 Electrochemical properties of lithium cobalt oxide materials

[0094] It can be seen from Table 1 that, compared with Example 1, in Example 2, the concentration of the acid solution in the lithium cobalt oxide pretreatment is higher, the degree of pickling is too high, and the first discharge specific capacity and the first coulombic efficiency are lower; while in Example 3, the concentration of the acid solution in the lithium cobalt oxide pretreatment is lower, the degree of pickling is too low, which reduces the primary coating effect of phosphate on the surface of lithium cobalt oxide, and the cycle performance of the obtained lithium cobalt oxide material at 25°C and 45°C is poor.

[0095] Compared with Examples 1-9, the lithium cobalt oxide material obtained in Comparative Examples 1-6 was not prepared completely according to the process of acid leaching, primary phosphate coating and secondary ammonium fluoride coating, so the first specific capacity, first coulomb efficiency or cycle performance at 25°C and 45°C and capacity retention rate after 30 days of storage of the obtained lithium cobalt oxide material were relatively poor. Among them, in Comparative Example 4, there was no coating treatment at all, and the first coulomb efficiency or cycle performance at 25°C and 45°C and capacity retention rate after 30 days of storage of the obtained lithium cobalt oxide material were much lower than those of other embodiments.

[0096] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A method for preparing a lithium cobalt oxide material, characterized in that: The preparation method comprises: Pretreatment of lithium cobalt oxide: dispersing lithium cobalt oxide in an acid solution for stirring reaction, and then filtering, washing and drying to obtain acid-treated lithium cobalt oxide; Primary coating: the acid-treated lithium cobalt oxide is mixed with phosphate and then sintered once to obtain primary coated lithium cobalt oxide; Secondary coating: The primary coated lithium cobalt oxide is mixed with ammonium fluoride salt and then sintered for a secondary time to obtain a lithium cobalt oxide material.

2. The preparation method according to claim 1, characterized in that: The acid in the acid solution includes at least one of oxalic acid, acetic acid, citric acid, phosphoric acid and carbonic acid; and / or, the phosphate comprises at least one of Li3PO4, LiCoPO4, LiFePO4, LiNiPO4, LiH2PO4, Co3(PO4)2 and LiH2PO4; And / or, the ammonium fluoride salt includes at least one of NH4BF4, (NH4)3AlF6, (NH4)2SiF6 and (NH4)2GeF6.

3. The preparation method according to claim 1 or 2, characterized in that: The molar concentration of the acid solution is 0.01-0.20 mol / L; and / or, the phosphate is 1wt%-3wt% of the acid-treated lithium cobalt oxide; And / or, the ammonium fluoride salt is 0.1wt%-0.5wt% of the primary coated lithium cobalt oxide.

4. The preparation method according to claim 1, characterized in that: The lithium cobalt oxide includes large-particle lithium cobalt oxide and small-particle lithium cobalt oxide, and the large-particle lithium cobalt oxide satisfies 18 μm≤D v 50≤21μm, the small particle lithium cobalt oxide satisfies 4.5μm≤Dv50≤9.5μm; The solid-liquid mass ratio of the lithium cobalt oxide to the acid solution is 1:1-3.

5. The preparation method according to claim 1, characterized in that: The primary sintering temperature is 500-900°C and the time is 3-6h; And / or, the secondary sintering temperature is 400-800°C and the time is 3-6h; And / or, the drying temperature is 60-120°C and the drying time is 24-30h; And / or, the stirring reaction time is 5-10 min.

6. The preparation method according to claim 2, characterized in that: The preparation process of the lithium cobalt oxide comprises: mixing a lithium source and an additive with large cobalt oxide particles and small cobalt oxide particles respectively, and then sintering and crushing them to obtain the large cobalt oxide particles and the small cobalt oxide particles respectively.

7. The preparation method according to claim 6, characterized in that: The large cobalt oxide particles satisfy the requirement of 13.5 μm≤D v 50≤18.5μm; And / or, the small particles of cobalt oxide satisfy 1.5 μm ≤ D v 50≤6.5μm; and / or, the additive is an oxide, the oxide comprising at least one of the elements Ti, Mg, Al, Y, La, Zr and B; And / or, the lithium source includes at least one of lithium carbonate and lithium hydroxide.

8. The preparation method according to claim 6 or 7, characterized in that: The mass of the additive is 0.3wt%-3.5wt% of the large cobalt oxide particles or the small cobalt oxide particles; and / or, the molar ratio of the lithium element in the lithium source to the cobalt element in the large cobalt oxide particles or the small cobalt oxide particles is 1.07-1.09; And / or, the sintering temperature is 1050-1100°C.

9. A lithium cobalt oxide material, characterized in that: The lithium cobalt oxide material is prepared by the preparation method according to any one of claims 1 to 8.

10. A secondary battery, characterized in that: The secondary battery comprises the lithium cobalt oxide material as claimed in claim 9.

Citation Information

Patent Citations

  • Method for coating nickel cobalt lithium manganate positive-electrode material with calcium fluophosphate

    CN103367723A

  • Fluorophosphate lithium ion-electron mixed conductor modified lithium cobaltate composite material and preparation method thereof

    CN106920947A

  • Germanium / fluorine / nitrogen co-doped lithium nickel cobalt manganate ternary positive electrode material and preparation method thereof

    CN111653762A

  • Coated modified lithium cobalt oxide positive electrode material, preparation method thereof and lithium ion battery

    CN118458839A

Cited By

  • Coated modified lithium cobalt oxide positive electrode material as well as preparation method and application thereof

    CN121306918A

  • High-energy-density rate type solid-liquid mixed lithium ion battery and preparation method thereof

    CN122315002A